Adsorption of Rhodamine B by Coconut Shell Activated Carbon - Siswanti, Siswanti; Dopinsa, Rexyvo Yurist Kusuma; Anggraita, Dwi (Eksergi, 2025)
Pollution caused by dye waste from the textile industry, specifically Rhodamine B, poses significant risks to human health. Furthermore, large-scale discharge of Rhodamine B into aquatic environments can alter water pH, thereby adversely affecting aquatic ecosystems. Environmental pollution caused by this dye can be prevented through adsorption using activated carbon. In this study aims to evaluate the efficiency of Rhodamine B dye removal from synthetic wastewater by varying the mass of activated carbon from coconut shell carbon and to determine the appropriate adsorption isotherm model based on the adsorption capacity of Rhodamine B on the adsorbent. The experiment was conducted by activating coconut shell carbon physically using a furnace at a temperature of 700℃ for 2 hours and chemically using 2.5 M KOH and soaked for 20 hours with a ratio of 1: 3 (m/v). The results of the study based on variations in adsorbent mass showed the best mass of 3 g with the smallest final concentration of 2.1717 ppm, an equilibrium time of 120 minutes, and an adsorption effectiveness of 86.13%. The appropriate adsorption isotherm model is the Langmuir isotherm.